Development of Microwave-Assisted Sulfonated Glucose Catalyst for Biodiesel Production from Palm Fatty Acid Distillate (PFAD) - Nur Nazlina Saimon; Mazura Jusoh; Norzita Ngadi; Zaki Yamani Zakaria (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Microwave-heating method for catalyst preparation has been utilized recently due to its shorter operation time compared to the conventional method. Glucose, a renewable carbon source can be partially carbonized and sulfonated via microwave heating which could result in highly potential heterogeneous carbon-based acid catalyst. In this study, the impacts of the carbonization and sulfonation parameters during the catalyst preparation were investigated. Catalysts prepared were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), X-Ray Diffraction (XRD), Brunauer-Emmet-Teller (BET), and Temperature Programmed Desorption–Ammonia (TPD-NH3). Analysis of the carbonization screening process discovered that the best incomplete carbonized glucose (ICG) prepared was at 20 minutes, 20 g of D(+)-glucose with medium microwave power level (400W) which exhibited the highest percentage yield (91.41%) of fatty acid methyl ester (FAME). The total surface area and acid site density obtained were 16.94 m2/g and 25.65 mmol/g, respectively. Regeneration test was further carried out and succeeded to achieve 6 cycles. The highest turnover frequency (TOF) of the sulfonated catalyst was methyl palmitate, 25.214´10−3 s−1 compared to other component of the methyl ester. Kinetic study was developed throughout the esterification process and activation energy from the forward and reverse reaction was 3.36 kJ/mol and 11.96 kJ/mol, respectively. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).